Perkembangan asimilasi seni reka motif Merong Mahawangsa dalam kesenian Melayu - Nurul Izzah Mohd Johari (Tanjong Malim, 2021)
Perkembangan asimilasi seni reka motif Merong Mahawangsa dalam kesenian Melayu by Nurul Izzah Mohd Johari